CLINICAL IMMUNOLOGY ASPECTS COMBINATION OF CYTOMEGALOVIRUS INFECTION AND TUBERCULOSIS - Smelyanskaya, M.V.; Poteyko, P.I.; Peremot, S.D. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In the article essential influence cytomegalovirus infections on formation immunodeficiency conditions, current and an outcome of tubercular process is proved. Rate of infectivity in CMV patients with a tuberculosis easy has made 83,9%, and at patients with the heaviest and tuberculosis dangerous forms has made100%. Presence of a syndrome the KIND on laboratory parameters diagnosed for 100% of patients with a tuberculosis and HCMV. Authors offer a way of complex treatment of a tuberculosis in view of viral persistence.